2020
DOI: 10.1111/jfd.13163
|View full text |Cite
|
Sign up to set email alerts
|

Koi herpesvirus and carp edema virus threaten common carp aquaculture in Croatia

Abstract: Common carp (Cyprinus carpio) is a very important fish species for warm‐water aquaculture in Croatia. All Croatian carp farms are subjected to a surveillance programme for the presence of koi herpesvirus (KHV), causing a deadly disease called koi herpesvirus disease (KHVD). However, there is no surveillance for other viral pathogens of importance like carp edema virus (CEV), a causative agent of koi sleepy disease (KSD). During regular testing within the KHVD surveillance programme, we tested samples for CEV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
(53 reference statements)
5
18
2
Order By: Relevance
“…Recently, Soliman et al (2019) presented new CEV sequences showing relatively low nucleotide identity with previously published isolates (43%-49%) and proposed the existence of a novel CEV genogroup III, also containing two older sequences by Ouyang et al (2018) and Ouyang et al (2020). On the contrary, additional investigation by Zrnčić et al (2020) showed that each sequence from the novel genogroup could be assigned to existing genogroups (I or II), when analysed in reverse complement form. Considering the possibility of the new sequences being uploaded in the reverse order, the existence of genogroup II as proposed by Soliman et al (2019), seems highly unlikely.…”
Section: Ta Xonomymentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, Soliman et al (2019) presented new CEV sequences showing relatively low nucleotide identity with previously published isolates (43%-49%) and proposed the existence of a novel CEV genogroup III, also containing two older sequences by Ouyang et al (2018) and Ouyang et al (2020). On the contrary, additional investigation by Zrnčić et al (2020) showed that each sequence from the novel genogroup could be assigned to existing genogroups (I or II), when analysed in reverse complement form. Considering the possibility of the new sequences being uploaded in the reverse order, the existence of genogroup II as proposed by Soliman et al (2019), seems highly unlikely.…”
Section: Ta Xonomymentioning
confidence: 98%
“…Before 2020, KSD/CEVD presence was reported in the following European countries: United Kingdom, Austria, Germany, Czech Republic, Slovakia, Hungary, Poland, Netherlands, France, Italy, Switzerland, Belgium, Serbia and Croatia (Adamek, Baska, et al, 2018;Bigarré & de Ploufragan-Plouzané, 2016;Haenen et al, 2013;Jung-Schroers et al, 2015;Lewisch et al, 2015;Matějíčková et al, n.d.;Matras et al, 2017;Pretto et al, 2015;Radosavljevic et al, 2018;Way et al, 2017;Zrnčić et al, 2020). Besides Japan, KSD/CEVD was confirmed in other Asian countries, namely India, Iraq, Republic of Korea, China and Thailand (Kim et al, 2018;Pikulkaew et al, 2020;Swaminathan et al, 2016;Toffan et al, 2020;Zhang et al, 2017).…”
Section: Epidemi Ologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the majority of sampling sites koi herpesvirus was confirmed as being the causative agent of death, in two locations CEV was identified as the only pathogen involved (Toffan et al., 2019). Similarly, mortality events occurred in lakes and ponds in Croatia in the period 2016–2019 and were associated with CEV detection (Zrnčić et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For a long time after these episodes, no other similar events were reported. The disease reappeared some years later, first in England (Way & Stone, 2013), followed by the Netherlands (Haenen et al., 2014), Austria (Lewisch et al., 2015), Brazil (Hesami et al., 2015), the Czech Republic (Vesely et al., 2015), Germany (Jung‐Schroers et al., 2015), Italy (Pretto et al., 2015), France (Bigarré et al., 2016), India (Swaminathan et al., 2016), China (Zhang et al., 2017), Hungary (Adamek et al., 2018), Poland (Matras et al., 2017), in the USA again (Padhi et al., 2019; Stevens et al., 2018), Korea (Kim et al., 2018), Iraq (Toffan et al., 2019), the Czech and Slovak Republic (Matějíčková et al., 2020) and Croatia (Zrnčić et al., 2020). In the majority of cases, farmed or traded common carp and koi were involved.…”
Section: Introductionmentioning
confidence: 99%